Guanine polynucleotides are self‐antigens for human natural autoantibodies and are significantly reduced in the human genome. Issue 3 (7th September 2015) - Fattal, Ittai; Shental, Noam; Ben‐Dor, Shifra; Molad, Yair; Gabrielli, Armando; Pokroy‐Shapira, Elisheva; Oren, Shirly; Livneh, Avi; Langevitz, Pnina; Zandman‐Goddard, Gisele; Sarig, Ofer; Margalit, Raanan; et al.
Summary In the course of investigating anti‐DNA autoantibodies, we examined IgM and IgG antibodies to poly‐G and other oligonucleotides in the sera of healthy persons and those diagnosed with systemic lupus erythematosus (SLE), scleroderma (SSc), or pemphigus vulgaris (PV); we used an antigen microarray and informatic analysis. We now report that all of the 135 humans studied, irrespective of health or autoimmune disease, manifested relatively high amounts of IgG antibodies binding to the 20‐mer G oligonucleotide (G20); no participants entirely lacked this reactivity. IgG antibodies to homo‐nucleotides A20, C20 or T20 were present only in the sera of SLE patients who were positive for antibodies to dsDNA. The prevalence of anti‐G20 antibodies led us to survey human, mouse and Drosophila melanogaster (fruit fly) genomes for runs of T20 and G20 or more: runs of T20 appear > 170 000 times compared with only 93 runs of G20 or more in the human genome; of these runs, 40 were close to brain‐associated genes. Mouse and fruit fly genomes showed significantly lower T20/G20 ratios than did human genomes. Moreover, sera from both healthy and SLE mice contained relatively little or no anti‐G20 antibodies; so natural anti‐G20 antibodies appear to be characteristic of humans. These unexpected observations invite investigation of the immune functions of anti‐G20 antibodies in human health and disease and of runs of G20 in the human genome.